Design and Hydrodynamic Performance Analysis of Airlift Sediment Removal Equipment for Seedling Fish Tanks - Yufei Zhang; Andong Liu; Chenglin Zhang; Chongwu Guan; Haigeng Zhang (Journal of Marine Science and Engineering)
This study innovatively proposes a pipeline-type pneumatic lift sediment removal device for cleaning pollutants at the bottom of fish breeding tanks and conducts hydrodynamic characteristic analysis on its core component, the pneumatic lift pipeline structure, which consists of a horizontal circular tube with multiple micro-orifices at the bottom and an upward-inclined circular tube. The pipeline has an inner diameter of 20 mm and a vertical length of 1.2 m, with the orifice at one end of the horizontal tube connected to the gas supply line. During operation, compressed gas enters the horizontal tube, generating negative liquid pressure that draws solid–liquid mixtures from the tank bottom into the pipeline, while buoyant forces propel the gas–liquid–solid mixture upward for discharge through the outlet. Under a constant gas flow rate, numerical simulations investigated efficiency variations through three operational scenarios: ① different pipeline orifice diameters, ② varying orifice quantities and spacings, and ③ adjustable pipeline bottom clearance heights. The results indicate that in scenario ①, an orifice diameter of 4 mm demonstrated optimal efficiency; in scenario ②, the eight-orifice configuration achieved peak efficiency; and scenario ③ showed that the proper adjustment of the bottom clearance height enhances pneumatic efficiency, with maximum efficiency observed at a clearance of 10 mm between sediment suction pipe and tank bottom.